Resilience of local communities to climate change around a ramsar site in Pakistan - Shelly, S. A.; Ali, Z.; Bibi, F.; Nasir, Zaheer A.; Colbeck, Ian; Butler, J. R. A. (Pakistan Agricultural Scientists Forum, 2015)
The Taunsa Barrage controls water flow in the River Indus for irrigation and flood control purposes. The river ecology is sensitive to climate change due to the high portion of its flow derived glacial melt. To assess the socio-economic status of the rural communities living within the Taunsa Barrage Wildlife sanctuary, a questionnaire was developed based on the perception of local communities about their resilience capacity and climate change. Temperature and rainfall data over the period 1951 – 2010 were analysed and used as an indicator of climate change. 85 of the respondents (n =100) reported that there had been an increase extreme climatic events over the past 60 years. These communities have proved to be resilient (94% n = 100) to it by changing occupations and lifestyles. However at the same time they have increased the pressure on natural resource use and this is causing a serious problem in the management of the protected area
Keywords: Pakistan; resilience; climate change; taunsa barrage; wildlife sanctuary; rural communities